Amplification-free, OR-gated CRISPR-Cascade reaction for pathogen detection in blood samples - Jongwon Lim; An Bao Van; Katherine Koprowski; Matthew Wester; Enrique Valera; Rashid Bashir (Proceedings of the National Academy of Sciences, 2025)
Rapid and accurate detection of DNA from disease-causing pathogens is essential for controlling the spread of infections and administering timely treatments. While traditional molecular diagnostics techniques like PCR are highly sensitive, they include nucleic acid amplification and many need to be performed in centralized laboratories, limiting their utility in point-of-care settings. Recent advances in CRISPR-based diagnostics (CRISPR-Dx) have demonstrated the potential for highly specific molecular detection, but the sensitivity is often constrained by the slow trans-cleavage activity of Cas enzymes, necessitating preamplification of target nucleic acids. In this study, we present a CRISPR-Cascade assay that overcomes these limitations by integrating a positive feedback loop that enables nucleic acid amplification-free detection of pathogenic DNA at atto-molar levels and achieves a signal-to-noise ratio greater than 1.3 within just 10 min. The versatility of the assay is demonstrated through the detection of bloodstream infection pathogens, including Methicillin-Sensitive Staphylococcus aureus (MSSA), Methicillin-Resistant Staphylococcus aureus (MRSA), Escherichia coli , and Hepatitis B Virus (HBV) spiked in whole blood samples. Additionally, we introduce a multiplexing OR-function logic gate, further enhancing the potential of the CRISPR-Cascade assay for rapid and accurate diagnostics in clinical settings. Our findings highlight the ability of the CRISPR-Cascade assay to provide highly sensitive and specific molecular detection, paving the way for advanced applications in point-of-care diagnostics and beyond.